Algorithm to design UWB pulse based on the peak frequency - ZOU Wei-xia1; ZHANG Chun-qing2; ZHOU Zheng1 (Tongxin xuebao)
A new pulse design algorithm was proposed to generate UWB pulse based on the relation among the peak frequency of Rayleigh monopulse, the pulse shape parameter α and the order of differentiation n. Not like other algorithms that only work out one pulse, the proposed algorithm can lead to the design of a myriad of pulses that are compliant, namely, it can figure out all α which satisfy the regulation and give out the range of α.